2000
DOI: 10.1080/00365510050216385
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and alternative nutrition - levels of homocysteine and lipid parameters in adults

Abstract: Values of homocysteine and lipid parameters were measured in groups of adults consuming alternative nutrition (vegetarians/lactoovo/, vegans) and compared with a group consuming traditional diet (omnivores, general population). Frequency of hyperhomocysteinemia was 53% in the vegans group, 28% in vegetarians vs. 5% in omnivores. In conditions of lower methionine intake (reduced content in plant proteins), the remethylation pathway of homocysteine metabolism prevails and it is vitamin B12 and folate-dependent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…This enzyme provides the conversion of ALA to stearidonic acid (substrate for EPA production by -5 desaturase activity). In group of iron deficient lacto-ovo-vegetarians vs. non-vegetarians and iron normal lacto-ovo-vegetarians we found the significantly reduced plasma concentrations of EPA and DHA (0.36 % vs. 0.57 % and 0.53 % EPA, 1.27 % vs. 1.80 % and 1.71 % DHA; fatty acids expressed as % from total fatty acids) (Krajčovičová-Kudláčková et al, 2000b).…”
mentioning
confidence: 69%
“…This enzyme provides the conversion of ALA to stearidonic acid (substrate for EPA production by -5 desaturase activity). In group of iron deficient lacto-ovo-vegetarians vs. non-vegetarians and iron normal lacto-ovo-vegetarians we found the significantly reduced plasma concentrations of EPA and DHA (0.36 % vs. 0.57 % and 0.53 % EPA, 1.27 % vs. 1.80 % and 1.71 % DHA; fatty acids expressed as % from total fatty acids) (Krajčovičová-Kudláčková et al, 2000b).…”
mentioning
confidence: 69%
“…The frequency of hyperhomocysteinemia was 53% in vegans and 28% in vegetarians vs. 5% in omnivores. It was concluded that low lipid risk factors but higher fi ndings of mild hyperhomocysteinemia in vegetarians indicated a diminished protective effect of alternative nutrition in cardiovascular disease prevention [Krajcovicová-Kudlácková et al, 2000].…”
Section: Benefits Of Vegetarianism Versus Risks Of Cerebrovascular DImentioning
confidence: 99%
“…It is also suggested that a vegan diet, despite the large quantities of herbal antioxidants, may increase the risk of oxidative stress due to an insufficient supply of vitamin B12 and increased levels of homocysteine, which in turn may increase the oxidative modification of lipids and risk of atherosclerosis [14].…”
Section: Introductionmentioning
confidence: 99%